A novel broadband dual-polarized antenna element for LTE700 MHz/GSM850 MHz/GSM900 MHz applications - He, Yejun (2018)
This paper presents a novel broadband and ±45° slant orthogonal dual-polarized antenna element designed for LTE700 MHz/GSM850 MHz/GSM900 MHz applications. The proposed antenna element consists of an annular base, four couples of baluns, three kinds of parasitic plastic fasteners (3 × 4 = 12, four for each kind of fastener), and four dipoles that are orthogonal with each other. Compared with the prototype without parasitic plastic fasteners, the impedance bandwidth of the proposed antenna element can be significantly improved. Measured results show that the proposed antenna element can operate from 698 to 960 MHz with VSWR <;1.7 at both ports, high port-to-port isolation of >25 dB, a stable radiation pattern with half-power beamwidth of 65.92° ± 5.44° at H plane and V plane, and a relatively stable gain of 9.41 ± 0.48 (dBi). In addition, the size of the proposed antenna element is 0.469λ 0 × 0.469λ 0 × 0.22λ 0 (λ 0 is the free-space wavelength referring to the antenna center frequency). Good agreement is observed between simulated and measured results.